2002
DOI: 10.1128/jvi.76.4.2024-2027.2002
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Expression Cassette of Lyssavirus Shows that the Distantly Related Mokola Virus Can Rescue a Defective Rabies Virus Genome

Abstract: By comparing three expression vectors for the rabies virus (Rv) minigenome, we show that the characteristic of the Rv RNA is important for efficient rescue despite its not being crucial for replication. Moreover, we show that the coexpression of the viral proteins from helper Rv and Mokola virus could rescue the Rv minigenome while Rv-related European bat lyssavirus 1 could not, suggesting that the signals controlling transcription and replication are conserved in the distantly related Rv and Mokola virus.Rabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 22 publications
1
29
0
Order By: Relevance
“…The luciferase gene reporter is framed by 3= leader and 5= trailer sequences and is under the control of rabies transcription signals (21). The production of luciferase activity is the result of the encapsidation of the minigenome followed by its transcription by the L-P complex and by its replication in the presence of N protein.…”
Section: And 18) This Indicates That the Drug Led To The Inhibition mentioning
confidence: 99%
See 3 more Smart Citations
“…The luciferase gene reporter is framed by 3= leader and 5= trailer sequences and is under the control of rabies transcription signals (21). The production of luciferase activity is the result of the encapsidation of the minigenome followed by its transcription by the L-P complex and by its replication in the presence of N protein.…”
Section: And 18) This Indicates That the Drug Led To The Inhibition mentioning
confidence: 99%
“…The plasmids pTit-N, pTit-P, and pTit-L were described previously (7) and were obtained from K. K. Conzelmann (Ludwig-Maximilians University of Munich). The plasmid pDImut (21) was provided by N. Tordo (Institut Pasteur). The plasmid pCMV-Hsp70, encoding the Hsp70 protein, and pCMV-Neo were kindly provided by G. Trugnan (2).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Earlier work indicated that the three extra cytidines introduced at the 5Ј end of the RV antigenome, which are needed for efficient transcription from the T7 RNA polymerase promoter, interfere with the efficient recovery of recombinant RVs (12,48). Our new system is based on the findings of Inoue et al that the creation of infectious RV is more efficient when a CMV promoter and two ribozymes flanking the antigenome are used (23,28). The data presented here showed that the improvement in the recovery frequency is probably due to the gener- ation of the precise 5Ј end of the antigenome.…”
Section: Discussionmentioning
confidence: 99%